68-12=4x

Simple and best practice solution for 68-12=4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 68-12=4x equation:


Simplifying
68 + -12 = 4x

Combine like terms: 68 + -12 = 56
56 = 4x

Solving
56 = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
56 + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
56 + -4x = 0

Add '-56' to each side of the equation.
56 + -56 + -4x = 0 + -56

Combine like terms: 56 + -56 = 0
0 + -4x = 0 + -56
-4x = 0 + -56

Combine like terms: 0 + -56 = -56
-4x = -56

Divide each side by '-4'.
x = 14

Simplifying
x = 14

See similar equations:

| 6v-5/8=7/8 | | -3(1+x)-6x=7-4x | | a/7+5/7=2/7 | | 7(y-1)=2(3y+1) | | x-2(2x+10)=12 | | 3x+7/2=8 | | A=2(l+1) | | 1/2(12n-8)=26 | | A=x+y | | -21+x=5+4(1+4x) | | 2/5(5k+35)-8=12 | | -2-2+4x=5-6x | | (4x-3)(5x+2)= | | -(2+11)=11-2t | | -3x-8+4x=-17 | | .4(3d-5)=4 | | x+-7=12 | | 2(4r+3)-3(r+5)= | | -3r+15= | | -(2n+6)=-3-3n | | x-(-1)=-5 | | 6x(5x+5)=-3 | | 3.8m-5-3.8m-3= | | 4(2h+1)+3(4h+7)= | | -9(5x+18)=243 | | 180=-6(7x+12) | | 4x+48=40+8+4x | | -312=-6(-7x-18) | | 9x-1*4x= | | -4x-4(x-1)=-32-4 | | 12+2p=3(4-5p) | | 2b-4-6b-6= |

Equations solver categories